Gouty arthritis: An approach for general practice - M. Tikly; K. Makan (South African Family Practice)
Gout is a common crystal-induced inflammatory arthritis, the prevalence and clinical complexity of which is increasing in the face of a growing aged population with multiple co-morbidities. Recent epidemiological studies emphasise that lifestyle factors strongly influence the development of hyperuricaemia and gout. Moreover, there is growing evidence that gout is an independent risk factor for cardiovascular disease. Acute attacks of gout are extremely painful and disabling, and if repeated attacks go untreated, chronic deforming arthritis ensues. Early diagnosis and appropriate therapy is essential to reduce long-term disability. Identification of monosodium urate crystals on synovial fluid analysis is the gold standard in gout diagnosis. Nonsteroidal anti-inflammatory drugs and oral or intra-articular corticosteroids remain central to the treatment of acute attacks. Prophylactic colchicine use, during the intercritical period, reduces gout flares, a common complication on initiation of urate-lowering therapy (ULT). Allopurinol is the treatment of choice when ULT is indicated. Gout management is suboptimal in many patients because of non-adherence to treatment and underutilisation of available treatments. Treating to target: a serum uric acid level 0.35mmol/l, prevents crystal deposition in joints and soft tissues, thereby preventing acute attacks and ongoing inflammation, as well as decreasing the size and number of tophi. Treatment strategies should include attention to cardiovascular risk. The family practitioner is paramount to gout management which should be individualised. Emphasis should be placed on ongoing education and prevention.